Plant genome : (Science Publishers ( SP ), 2004)
In introducing a dozen contributions by scientists from ten countries, the Sharmas (Centre of Advanced Study on Cell and Chromosome Research, and botany, respectively, U. of Calcutta) note the lack of a comprehensive series on plant genomics despite the data surge in this field. In the debut volume of a series intended to redress this gap, authors review the results of application of molecular and traditional techniques in the study of the phylogeny, taxonomy, and distribution of such key plant groups as Brassicaceae, Triticeae, and Rosaceae. Includes color figures. Distributed by Enfeld.